Development of a Disease Progression Model for Leucine‐Rich Repeat Kinase 2 in Parkinson's Disease to Inform Clinical Trial Designs. Issue 3 (5th December 2019) - Ahamadi, Malidi; Conrado, Daniela J; Macha, Sreeraj; Sinha, Vikram; Stone, Julie; Burton, Jackson; Nicholas, Timothy; Gallagher, Jill; Dexter, David; Bani, Massimo; Boroojerdi, Babak; Smit, Hans; et al.
Abstract : A quantitative assessment of Parkinson's disease (PD) progression is critical for optimizing clinical trials design. Disease progression model was developed using pooled data from the Progression Marker Initiative study and the Incidence of Cognitive Impairment in Cohorts with Longitudinal Evaluation in Parkinson's Disease study. Age, gender, concomitant medication, and study arms were predictors of baseline. A mutation in the leucine‐rich repeat kinase 2 ( LRRK2 ) encoding gene was associated with the disease progression rate. The progression rate in subjects with PD who carried LRRK2 mutation was slightly slower ( 0.170 points/month) than that in PD subjects without the mutation ( 0.222 points/month). For a nonenriched placebo‐controlled clinical trial, approximately 70 subjects/arm would be required to detect a drug effect of 50% reduction in the progression rate with 80% probability, whereas 85, 93, and 100 subjects/arm would be required for an enriched clinical trial with 30%, 50%, and 70% subjects with LRRK2 mutations, respectively.